ABCC6 MISSENSE MUTATION AND SEVERE RESISTANT SYSTEMIC HYPERTENSION IN A CHILD. - M, Thendral; k, Supreetha (Pediatric Review: International Journal of Pediatric Research, 2025)
Pseudoxanthoma elasticum (PXE) is a rare multisystem disorder characterised by progressive calcification and fragmentation of elastic fibres. Recent genetic advances have identified the underlying defect in the ABCC6 gene on chromosome 16p13.1. Patients typically develop cutaneous, ocular, and cardiovascular manifestations, but there is considerable phenotypic variability. Skin changes are usually apparent in adulthood and rarely observed in childhood. Since the prognosis of PXE largely depends on the extent of extracutaneous organ involvement, early recognition, intervention, and lifestyle adjustments are important to reduce morbidity.